Analysis of defects associated with leaks on skid steer loaders - Imel, Clint J. (Kansas State University, 2010)
The CNH Wichita Product Center has had a chronic leak problem with the Skid Steer Loaders. The objective of this project was to analyze the manufacturing plant leak data and make improvements to correct the issue. The objective is twofold: 1) to make process or design improvements on current products produced in the plant and 2) to make recommendations for future designs to prevent such leak issues from reoccurring. The manufacturing data had to be transformed into usable form and then it was analyzed mostly by utilizing Pareto Charts. The highest six problem leak points were chosen from the manufacturing data. Process changes were implemented on these particular leak joints and the results were analyzed using two proportions hypothesis tests. The process changes reduced the leak rate by an average percent reduction of 86 percent. The process changes implemented will also be applied to other similar joints, and results documented in the future. The future design recommendations made from the analyzed data included the increased use of o-ring face seal connections at certain locations and where possible, reducing the number of joints per machine.
Keywords: Defect analysis; Manufacturing defects; Manufacturing process control; Economics, Agricultural (0503)